2014
DOI: 10.1093/ejcts/ezu098
|View full text |Cite
|
Sign up to set email alerts
|

Delayed therapy with clopidogrel and everolimus prevents progression of transplant arteriosclerosis and impairs humoral alloimmunity in murine aortic allografts

Abstract: These results demonstrate that delayed treatment with clopidogrel and everolimus-representative of a clinical setting-prevents the progression of transplant arteriosclerosis and impairs humoral immunity in this experimental model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 24 publications
0
10
1
1
Order By: Relevance
“…However, a delayed anti-platelet therapy, when atherosclerotic lesions are already present, was only able to ameliorate the process of plaque formation to a certain extent, but did not result in significant reverse remodelling within the vascular wall. These findings are in contrast to the results from a murine aortic transplant model, where the progress of intima proliferation is significantly reduced even when vascular lesions were already present [28]. We would speculate at this stage that the time point of delayed clopidogrel administration in this study may have been too late to reach significant levels of progress reduction.…”
Section: Discussioncontrasting
confidence: 99%
“…However, a delayed anti-platelet therapy, when atherosclerotic lesions are already present, was only able to ameliorate the process of plaque formation to a certain extent, but did not result in significant reverse remodelling within the vascular wall. These findings are in contrast to the results from a murine aortic transplant model, where the progress of intima proliferation is significantly reduced even when vascular lesions were already present [28]. We would speculate at this stage that the time point of delayed clopidogrel administration in this study may have been too late to reach significant levels of progress reduction.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been shown that monotherapy with clopidogrel can effectively reduce the formation of transplant arteriosclerosis in a murine aortic allograft model . Furthermore, delayed treatment with clopidogrel and everolimus prevents the progression of transplant arteriosclerosis and impairs humoral immunity in murine aortic allografts . Ticlopidine showed profound suppression of platelet aggregation .…”
Section: Discussionmentioning
confidence: 99%
“…38 For example, a report showed that a delayed anti-platelet therapy with clopidogrel and everolimus prevents progression of transplant arteriosclerosis in murine aortic allografts. 39 …”
Section: Discussionmentioning
confidence: 99%